Geochronology of the Late Cretaceous magmatism and metamorphism, Puturge massif, Turkey - Kilic, Ayse Didem; Ates, Cihat (Science Press, 2015)
The Puturge massif was developed within the south branch of Neotethys, and it is possibly one of the terranes within the Late Cretaceous collisional zone between the Eurasia and Arabian plates. Regional metamorphic rocks of the Puturge massif mainly include metapelitic schist, metapelitic gneiss, granitic gneiss, quartzite, amphibolite and marble. A Barrovian-like prograde sequence is found in the metapelites in this terrane, and metamorphic peak of this massif reached upper greenschist to amphibolite facies conditions. SIMS U-Pb age of 84.2 +/- 1.1 Ma of the zircons was obtained from the metagranitic gneiss of the Puturge massif suggests that the magmatism occurred at the Upper Cretaceous Santonian time, and 39Ar/40Ar age of the biotites separated from the metapelitic schist was determined to be 83.21 +/- 0.069 Ma. These geochronological data suggest that the metamorphism occurred immediately after the magmatism.
Keywords: Puturge metamorphic massif; U-Pb age; 40Ar/39Ar age; Neotethys evolution; Turkey